The Culture of Immodesty in American Life and Politics
VI, 228 p.
Keywords: By identifying and illustrating aspects of American culture that are out of sync with the modest republicanism that gave rise to the United States in the late eighteenth century, the contributors to this volume expose the vulgarity and excess of American culture.